PENGARUH TERAPI OLAHRAGA YOGA TERHADAP TEKANAN DARAH DAN KADAR HEMOGLOBIN LANSIA DI BRSL GAU MABAJI KABUPATEN GOWA - Ahmad Akbar Ismail; Arimbi Arimbi; Abdul Rahman (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2022)
This research is an experimental research which aims to find out (1). the effect of exercise therapy yoga on the blood pressure of the elderly in BRSL Gau Mabaji, Gowa Regency. (2) the effect of exercise therapy yoga on the hemoglobin levels of the elderly in BRSL Gau Mabaji, Gowa Regency. bound are blood pressure and hemoglobin levels. The population in this study was 1093 people while the sample consisted of 30 people. The research data were obtained using blood pressure and hemoglobin levels. The data analysis technique used is statistics using computer facilities through the SPSS program with a simple regression test. Based on the results obtained systolic value obtained t value 8.851 with a significance value of 0.000. It turns out that the significant value obtained is 0.000 less than 0.05. It can be concluded that Ha is accepted and Ho is rejected. It can be concluded that the hypothesis is accepted, meaning that there is an effect of exercise therapy yoga on the blood pressure of the elderly at BRSL Gau Mabaji, Gowa Regency. And diastolic systolic t value obtained 3.436 with a significance value of 0.002. It turns out that the significant value obtained is 0.002 less than 0.05. It can be concluded that Ha is accepted and Ho is rejected. It can be concluded that the hypothesis is accepted, meaning that there is an effect of exercise therapy yoga on the blood pressure of the elderly in BRSL Gau Mabaji, Gowa Regency. It turns out that the significant value obtained is 0.000 less than 0.05. It can be concluded that Ha is accepted and Ho is rejected. It can be concluded that the hypothesis is accepted, meaning that there is an effect of exercise therapy yoga on the hemoglobin levels of the elderly in BRSL Gau Mabaji, Gowa Regency, so it can be concluded that (1). There is an effect of exercise therapy yoga on the blood pressure of the elderly in BRSL Gau Mabaji, Gowa Regency. (2) There is an effect of exercise therapy yoga on the hemoglobin level of the elderly in BRSL Gau Mabaji, Gowa Regency.